2018
DOI: 10.1136/bmj.k499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of untreated cervical intraepithelial neoplasia grade 2 under active surveillance: systematic review and meta-analysis

Abstract: ObjectiveTo estimate the regression, persistence, and progression of untreated cervical intraepithelial neoplasia grade 2 (CIN2) lesions managed conservatively as well as compliance with follow-up protocols.DesignSystematic review and meta-analysis.Data sourcesMedline, Embase, and the Cumulative Index to Nursing and Allied Health Literature (CINAHL) from 1 January 1973 to 20 August 2016.Eligibility criteriaStudies reporting on outcomes of histologically confirmed CIN2 in non-pregnant women, managed conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
263
5
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(286 citation statements)
references
References 74 publications
11
263
5
7
Order By: Relevance
“…Interestingly, we observed that CIN2 was more prevalent in younger ages compared to CIN3, in screened population. This observation is in line with natural history studies, which indicated that CIN2 is more likely to regress and is, therefore, more common at younger ages . While persistent HPV infection initiates the natural history of cervical cancer, and CIN3 is considered a real precancerous lesion, diagnosis of CIN2 is poorly reproducible.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, we observed that CIN2 was more prevalent in younger ages compared to CIN3, in screened population. This observation is in line with natural history studies, which indicated that CIN2 is more likely to regress and is, therefore, more common at younger ages . While persistent HPV infection initiates the natural history of cervical cancer, and CIN3 is considered a real precancerous lesion, diagnosis of CIN2 is poorly reproducible.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, natural history studies, in which cervical intra-epithelial neoplasia grade 2 and 3 lesions were distinguished based on conventional pathological criteria, show a much higher spontaneous regression rate for grade 2 (40–74%) than for grade 3 lesions (22–33%) 6 33. Other studies confirm the high regression rate of grade 2 lesions 34. Based on these results, guidelines now advise on observational management of cervical intra-epithelial neoplasia grade 2 in younger women, to reduce overtreatment and associated long-term obstetric complications 9.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, the relationship between CIN2 and cervical cancer is not clear-cut. Most CIN2 lesions in women below age 30 regress spontaneously; an active surveillance approach has therefore been recommended for this group 16. The Cochrane review’s 26 trials mainly included women below age 30 and used frequent cervical screening (often every six months) that did not reflect real-life practice (often every three to five years6).…”
Section: The Included Hpv Vaccine Trials Used Composite Surrogate Outmentioning
confidence: 99%